PENGARUH KUALITAS PRODUK TABUNGAN DAN KUALITAS LAYANAN TERHADAP MINAT MENABUNG KEMBALI DI CIMB NIAGA (STUDI KASUS PT BANK CIMB NIAGA TBK BINTARO) - Dedy Trisnadi (Universitas Mercu Buana, 2013)
Abstract: The purpose of this research was to determine the effect of product quality and service quality savings on interest savings back partially and simultaneously. The population in this study is that customers save at CIMB Niaga branch Bintaro, while the sample is 100 respondents. The sampling technique was purposive sampling. Type of data used is primary data correlation and multiple regression analysis.The results showed that the quality of the product has a positive effect on savings interest savingsback. Dominant factor affecting the interest saving back customers is the quality of the product.Keywords: Savings Product Quality, Service Quality, Savings Interest.